Les enseignants du supérieur face à l’enseignement en ligne « obligé » - Jacques Audran (Centre National d'Enseignement à Distance, 2021)
The lockdown of higher education institutions in the European spring semester 2020 required an emergency migration to online teaching. Although support was offered to lecturers, the necessity to adapt to the situation remained in charge of them. This particular situation offers the opportunity to better understand the complexity of the challenge faced by the teachers and the possible evolution of their relationship to digital education. The main goal of this paper is to highlight the teachers’ first reactions, their priorities, and any changes in their relationship to educational technologies. Lecturers and teachers from three universities (N= 616) from the Upper Rhine region in Switzerland and France completed an online survey just after the spring 2020 lockdown. The questionnaire asked them about their practices and their feelings over three periods: before the lockdown, the period of switching to online lessons, and after lockdown. The first results show the effects produced by this massive use of online education and first and foremost the need to maintain the relationship with the students. They also suggest that the pandemic has improved the acceptability of online education, without ensuring its sustainable adoption.